Indigenous Concepts of Education : Toward Elevating Humanity for All Learners - Wyk, Berte van; Adeniji-Neill, Dolapo; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2014)
Featuring in-depth examinations of concepts of knowing, learning, and education from a range of cultures worldwide, this book offers a rich theory of indigenous concepts of education, their relation to Western concepts, and their potential for creating education that articulates the aspirations of communities and fosters humanity for all learners.
Keywords: Science; Science, general